Mixed Model Assembly Line Balancing With Sub-Assembly Selection in Automotive Industry - Özdemir, Rifat Gürcan; Kula, Ufuk (World Scientific Publ Co Pte Ltd, Po Box 128 Farrer Rd, Singapore 9128, Singapore, 2012)
In this study, mixed model assembly line balancing and sub-assembly selection problems are solved jointly. The mixed model assembly line balancing problem requires that tasks are assigned to workstations with balanced workloads. In sub-assembly selection problem, manufacturer determines which components of the products are assembled in sub-assembly area and which ones are assembled on the products directly in the line. Sub-assembly alternatives, task times, precedence relations and other system specific data are input to determine which tasks are assigned to sub-assembly area and which ones are assigned to the line for two conflicting objectives of minimizing cycle time and minimizing total cost. A recursive two stage goal programming approach is developed to solve the above mentioned problem. The developed model is then implemented in a real life automotive manufacturer's assembly line balancing problem.